Diagenesis of plattenkalk: Examples from the Solnhofen area (Upper Jurassic, southern Germany) - Munnecke, Axel; Westphal, Hildegard; Kölbl-Ebert, Martina (Sedimentology, 2008)
The Upper Jurassic (Tithonian) plattenkalk successions in the Solnhofen/ Eichstätt area consist of alternations of thin-bedded, laminated, fine-grained, very pure limestones (so-called 'flinz beds') and softer interlayers with slightly lower carbonate contents that are also laminated and show a foliaceous weathering appearance ('fäule beds'). These successions are world famous for their exceptionally well-preserved fossils. In contrast to the well-studied wealth of fossils, little is known about the origin and diagenesis of the host rock. The reason for this discrepancy might lay in the monotonous appearance of these fine-grained mudstones that require electron microscopical examination. Study of samples from the Solnhofen-Eichstädt area implies that flinz and fäule beds have undergone differential diagenesis. The ultrastructure of the flinz beds is characterized by interlocking microspar crystals, whereas the fäule beds show smaller and less interlocking crystals. The ratios of diagenetically inert trace elements lack clear differences between the two interlayered lithologies. While most authors agree that the flinz-fäule rhythm reflects rhythmically changing environmental conditions, primary rhythms can be taken as proven only where statistically significant differences in diagenetically resistant proxies are found. The absence of clear primary differences between flinz and fäule beds, however, leaves the question of primary differences unsolved. It is concluded that diagenesis has had a strong influence on the genesis of the lithological rhythm, and that any primary rhythm underlying the diagenetically mature rhythm is less clear than generally assumed. © Journal compilation © 2008 International Association of Sedimentologist
Keywords: Upper Jurassic; Tithonian; Plattenkalk; Solnhofen; Diagenesis